Comparing the Effects of Continuous Hormone Replacement Therapy and Tibolone on the Genital Tract of Menopausal Women; A Randomized Controlled Trial - S Ziaei; R Masoumi; S Faghihzadeh (JRI, 2010)
Introduction: Many postmenopausal women who are on hormone replacement therapy discontinue medications due to vaginal bleeding. Tibolone, a synthetic steroid, has minimal stimulatory effect on the endometrium. The aim of this study was to assess the effects of continuous HRT regimen and tibolone on the onset of vaginal bleeding and vaginal maturation value. Materials and Methods: A total of 150 healthy women in postmenopausal period were randomly enrolled in this controlled clinical trial. Patients were randomly allocated into three groups, and were followed for six months. The first 50 women received 2.5 mg tibolone plus a Cal+D tablet (500 mg Calcium and 200 IU vitamin D) daily, the second 50 women received 0.625 mg conjugated equine estrogen and 2.5 mg medroxyprogesterone acetate (CEE/MPA) plus one Cal+D tablet daily, and the remaining 50 received only one Cal+D tablet per day and served as the control group. Symptoms were recorded using a questionnaire that assessed vaginal bleeding or spotting, vaginal dryness and intention to continue the medications. Vaginal maturation value was assessed by examining vaginal smears before and after the treatment. The results for the three groups were analyzed using statistical methods. Results: In comparison with the control group, CEE/MPA and tibolone increased vaginal maturation value and decreased the frequency of vaginal dryness (p < 0.01). Women in tibolone group were more likely to continue the treatment regimen than those in the CEE/MPA or the control groups (p < 0.01). Conclusion: Tibolone can serve as an appropriate choice for HRT as it has low rates of vaginal bleeding/ spotting episodes and high acceptance rate in postmenopausal women.
Keywords: Calcium, Hormone replacement therapy, Menopause, Tibolone, Vaginal bleeding, Vaginal maturation value